PENGARUH LATIHAN ABDOMINAL STRETCHING TERHADAP INTENSITAS DISMENORE - Syafna, Annisa; Dewi, Yulia Irvani; Hairani Damanik, Siti Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Dysmenorrhea is one of the most common gynecological problems experienced during adolescence, is very disturbing activities and often require the patient to rest and leave the activity. This study was aimed to determine the influence of abdominal stretching exercise against intensity of dysmenorrhoe. The design of this research study was